Multipodal arrangement of push–pull chromophores: a fundamental parameter affecting their electronic and optical properties. (16th January 2017) - Klikar, M.; Kityk, I. V.; Kulwas, D.; Mikysek, T.; Pytela, O.; Bureš, F.
Abstract : Branching, along with the acceptor nature and π-system length, was revealed as a crucial factor affecting the fundamental optoelectronic properties of push–pull molecules. Abstract : A series of model push–pull molecules with linear, quadrupolar, and tripodal arrangements, a varyingly substituted amino donor, two acceptors, and a partially extended π-system has been prepared. Two peripheral electron acceptors, namely N, N ′-dibutylbarbituric acid and dicyanovinyl, were employed. The fundamental properties of 24 push–pull chromophores were investigated by differential scanning calorimetry, electrochemistry, one-photon absorption spectroscopy, photoinduced piezooptics, and were supported by DFT calculations. Thorough structure–property relationships were elucidated, while a significant influence of the structural arrangement/branching on the electronic and optical properties has been revealed. The fundamental optoelectronic properties of push–pull molecules are affected by their arrangement (linear/quadrupolar/tripodal), the peripheral acceptor attached, extension and planarization of the π-system, and also by the type of auxiliary N -substituent.